Student Values, Religiosity, and Pro-social Behaviour: A Cross-national Perspective - Cnaan, R.; Pessi, A.; Zrinšcak, S.; Handy, F.; Brudney, J.; Grönlund, H.; Haski-Leventhal, D.; Holmes, Kirsten; Hustinx, L.; Kang, C.; Kassam, M.; Meijs, L.; et al. (Vandenhoeck & Ruprecht GmbH & Co., 2012)
The association between altruistic values, religious values and pro-social behaviour is well documented, though mainly in North America and across disparate demographic groups. However, we currently have no data that focus on the relationships between personal values, religious values and pro-social behaviour across many different countries. Our study provides this data. We surveyed the values and pro-social behaviour (giving donations and volunteering) of university students in 14 different countries, thus achieving a unique cross-national perspective. We also included questions about materialistic values, which have hitherto been largely assumed to cause a reduction in pro-social behaviour. Our findings show that altruistic and religious values are positively significant in explaining variations in pro-social behaviour, but that materialistic values are not negatively correlated with pro-social behaviour. Our study thus suggests that, in the modern world, materialistic, religious and altruistic values can combine in complex ways to determine pro-social behaviour and that this combination varies across countries and cultures. In the discussion section, we draw conclusions that also relate to religious institutions and their diaconia.